Transferts, hybridations et renouvellements des savoirs. Parcours urbanistique et architectural de Michel Écochard de 1932 à 1974 - Marlène Ghorayeb (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The journey of Michel Écochard serves as a great example of exported expertise in urban planning. Throughout his entire career, he intervened in various countries in the Middle and Near East, as well as in Africa, becoming a worthy representative of the International Congress of Modern Architecture (CIAM) in Morocco. From the outset, he claimed without ambiguity to be the spokesperson for French expertise, both in architecture and urban planning. He advocated for the implementation of the modern movement’s principles as well as urban theories which marked the development of cities in the post-war years. Just after graduation in 1935, Michel Écochard was employed by the French mandate’s administration in the Levant. In Morocco, he put modern theories to the test of local data and the problem of slums, and developed innovative solutions for "housing in great numbers". After 1955, he pursued his international career in Africa and in the Near East, where he conducted urban development plans and large-scale projects, most notably in schools, universities and hospital facilities. This article will shed light on the journey of this iconic figure in exporting architecture and urbanism at the interface of cultures in order to reveal the richness engendered by the interconnection of his various experiences.